Antithrombotic Therapy for Secondary Prevention in Patients with Non-Cardioembolic Stroke or Transient Ischemic Attack: A Systematic Review - Dániel Tornyos; Alexandra Bálint; Péter Kupó; Oumaima El Alaoui El Abdallaoui; András Komócsi (Life, 2021)
Stroke embodies one of the leading causes of death and disability worldwide. We aimed to provide a comprehensive insight into the effectiveness and safety of antiplatelet agents and anticoagulants in the secondary prevention of ischemic stroke or transient ischemic attack. A systematic search for randomized controlled trials, comparing antiplatelet or anticoagulant therapy versus aspirin or placebo among patients with ischemic stroke or transient ischemic attack, was performed in order to summarize data regarding the different regimens. Keyword-based searches in the MEDLINE, EMBASE, and Cochrane Library databases were conducted until the 1st of January 2021. Our search explored 46 randomized controlled trials involving ten antiplatelet agents, six combinations with aspirin, and four anticoagulant therapies. The review of the literature reflects that antiplatelet therapy improves outcome in patients with ischemic stroke or transient ischemic attack. Monotherapy proved to be an effective and safe choice, especially in patients with a high risk of bleeding. Intensified antiplatelet regimens further improve stroke recurrence; however, bleeding rate increases while mortality remains unaffected. Supplementing the clinical judgment of stroke treatment, assessment of bleeding risk is warranted to identify patients with the highest benefit of treatment intensification.